Emballonurid bats from Colombia: Annotated checklist, distribution, and biogeography - Mantilla-Meluk, Hugo; Ramírez-Chaves, Héctor E.; Jiménez-Ortega, Alex M.; Rodríguez-Posada, Miguel E. (THERYA, 2014)
Introduction: Genetic data hypothetically place the origin of the most recent common ancestor of the subfamily Emballonurinae in Africa, suggesting a dispersal event from Africa to South America during the Oligocene (30 Ma), and a subsequent allopatric radiation in the New World. Emballonurid genera exist in Central America where, to date, only one event of diversification has been documented for Balantiopteryx before the completion of the Isthmus of Panama land connection in the Pliocene. Methods: Emballonurid bats constitutes an important element of the bat fauna in Colombia. Herein, museum voucher specimens were used as primary source to generate a checklist of emballonurid bats from Colombia. In addition, selected museum voucher specimens were analyzed to verify their identifications. The checklist is accompanied by references as well as models of potential distribution for each Colombian emballonurid species. These distribution maps were used to investigate the affinities, in species composition, among Colombian ecoregions as outlined by Hernández-Camacho et al. (1992), and to determine emballonurid richness distribution in Colombia and the relationship between environmental variables and patterns of species richness in this group of bats in the country. Results: We report 16 confirmed emballonurid bat species for Colombia and three species potentially present in the country, for a total of 19 species representing the eight recognized Neotropical emballonurid genera. At 16 known species, Colombia has the second greatest number of Neotropical emballonurid bats after Brazil (17 spp.). Discussion and conclusion: The checklist presented herein is accompanied by 11 taxonomic and distributional comments explaining recent changes in taxonomy, species distribution rearrangements, as well as clarifications and a refinement of the previous records for Colombia. In addition, Geographic Information System (GIS) models of potential distribution were created for all confirmed species in Colombia, and species richness patterns were analyzed. Finally, in a Parsimony Analysis of Endemism was performed for Colombian emballonurids we found that diversity within this group of bats in geographically subdivided in Colombia into four main regions including: The Biogeographic Chocó; the Magdalena Valley; The Orinoquia; and the Guianan-Amazon region. Key words: Chiropterans, Parsimony Analysis of Endemism, sheath-tailed bats, sac-wing bats, distribution maps.